2012
DOI: 10.1002/bjs.8942
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled volatile organic compounds identify patients with colorectal cancer

Abstract: Background: An effective screening tool for colorectal cancer is still lacking. Analysis of the volatile organic compounds (VOCs) linked to cancer is a new frontier in cancer screening, as tumour growth involves several metabolic changes leading to the production of specific compounds that can be detected in exhaled breath. This study investigated whether patients with colorectal cancer have a specific VOC pattern compared with the healthy population.Methods: Exhaled breath was collected in an inert bag (Tedla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
200
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(217 citation statements)
references
References 33 publications
8
200
1
1
Order By: Relevance
“…20 In recent years, many investigations have focused on analyzing CRC by determining the urinary metabolic profiles, blood levels of water-soluble metabolites, and exhaled VOCs of CRC patients. 8,15,21 To the best of our knowledge, no study has investigated the specific volatile metabolic biomarkers that exist in the blood of CRC. Chen performed a metabolomics analysis of the effects of CRC on urine and determined that relative to the urine of a control group of healthy individuals, the urine of CRC patients exhibited significantly higher levels of lactic acid but lower levels of histidine and methionine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 In recent years, many investigations have focused on analyzing CRC by determining the urinary metabolic profiles, blood levels of water-soluble metabolites, and exhaled VOCs of CRC patients. 8,15,21 To the best of our knowledge, no study has investigated the specific volatile metabolic biomarkers that exist in the blood of CRC. Chen performed a metabolomics analysis of the effects of CRC on urine and determined that relative to the urine of a control group of healthy individuals, the urine of CRC patients exhibited significantly higher levels of lactic acid but lower levels of histidine and methionine.…”
Section: Discussionmentioning
confidence: 99%
“…28 Altomare et al also identified various CRC-specific VOCs, including 2-methylbutane, cyclohexane, decanal, 4-methyl-2-pentanone, 1,2-pentadiene, 2-methylpentane, 4-methyloctane, methylcyclopentane, 3-methylpentane, methylcyclohexane, 1,3-dimethylbenzene, 1,4-dimethylbenzene, and nonanal. 15 These volatile biomarkers are mostly alkanes, ketones, aldehydes, and substituted benzene compounds. The mechanisms through which these metabolites are generated remains under investigation, although the majority of the extant studies support the hypothesis that these metabolites are produced in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study recently published in the British Journal of Surgery provides new hope in this direction claiming that a breath analysis could earn a spot in the range of different screening tests for early detection of CRC [14]. The breath samples collected from 37 patients with histologically proven colorectal cancer, in addition to 41 healthy volunteers, were analyzed to assess how they differ in VOC composition.…”
mentioning
confidence: 99%